Воспроизводство населения и демографическая политика в СССР - Борисов В. А. Владимир Александрович; Киселева Г. П.; Лукашук Ю. М.; Синельников А. Б; Рыбаковский Л. Л. Леонид Леонидович (Москва, Наука, 1987)
Авт. указаны на обороте тит. л.